The tell-tale horse : a novel - Brown, Rita Mae (Brown, Rita Mae. Sister Jane foxhunting mysteries, 2007)
When the body of a murdered woman is discovered naked and bound to an equine statue, Sister Jane discovers a link between the victim and a member of the Jefferson Hunt Club, but her investigation is complicated when another woman turns up dead.